2004
DOI: 10.1108/00907320410537702
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging collaboration for information literacy in psychology

Abstract: A case study of the integration of information literacy into a psychology research course is presented. The process of integration began with developing learning outcomes, a fourhour curriculum, exercises, and an assessment instrument, which were approved by the Psychology Department's undergraduate curriculum committee. Also emphasized is the ongoing exchange of expertise between liaison librarian and psychology faculty to enhance library-related components in the design of the course. Difficulties in impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…They threw out half the content of the course and spend more time teaching students how to obtain, interpret, and use data. Thaxton, Faccioli, and Mosby (2004) reported some success shaping student information literacy skills in an undergraduate psychology research methods course when four contact hours over two class periods were devoted to instruction and hands-on exploits. The availability and willingness of librarians to collaborate with and support both disciplinary faculty and students in advancing these skills makes for a more robust community of learners, enhancing the effectiveness of faculty and increasing the likelihood of student growth and transformation.…”
Section: Discussionmentioning
confidence: 97%
“…They threw out half the content of the course and spend more time teaching students how to obtain, interpret, and use data. Thaxton, Faccioli, and Mosby (2004) reported some success shaping student information literacy skills in an undergraduate psychology research methods course when four contact hours over two class periods were devoted to instruction and hands-on exploits. The availability and willingness of librarians to collaborate with and support both disciplinary faculty and students in advancing these skills makes for a more robust community of learners, enhancing the effectiveness of faculty and increasing the likelihood of student growth and transformation.…”
Section: Discussionmentioning
confidence: 97%
“…This continuous collaboration led to the eventual implementation of the library instruction program. The students were given pretests and posttests, and the students' posttests indicated that students benefited from the information literacy instruction (Thaxton, Faccioli, and Mosby 2004).…”
Section: The Social and Behavioral Sciencesmentioning
confidence: 99%
“…There were only a few efforts to create Psychology-specific information literacy instruction (e.g. Lampert, 2005;Thaxton et al, 2004). This is not surprising, as relevant ACRL Psychology Information Literacy Standards have just become established recently (ACRL, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, there is no standardized Psychology-specific information literacy test publicly available for which psychometric properties have been reported. Thaxton et al (2004) mentioned that an evaluation instrument has been used to evaluate the information literacy training; however, neither the instrument nor its psychometric properties are reported. Another study evaluated an information literacy training for Psychology students by asking students to prepare a literature search plan (Larkin and Pines, 2005).…”
Section: Introductionmentioning
confidence: 99%